Rapid prototyping of craniofacial structures (2008)
This article presents a description of the Rapid Prototyping (RP) technology applied to medicine, specifically to craniofacial problems, with which solid 3D models can be manufactured by adding material. In turn, an application is described from the simulation of a surgery to insert four mandibular implants, which constitute the basis of a fixed prosthesis supported by implants. The simulation of the surgical procedure began with the obtaining of the mandibular geometry from the processing of biomedical images, coming from a Computerized Axial Tomography (CT) of an adult woman, totally edentulous. This process was carried out using the GIB Points 3D software, developed within this work. With the software a text file was obtained with the cloud of 3D points of the jaw that was subsequently exported to ProEngineer Wildfire 3.0, from which a file was generated in standard STL format, compatible with most RP machines. The technology used for 3D printing was that of "deposition of molten wire" or Fused Deposition Modeling (FDM). It was possible to obtain a plastic model of a jaw, of great anatomical and dimensional quality, using technology available in Colombia. In addition, the surgical procedure for the installation of four implants was successfully simulated using the tools that would be used in the actual surgery. In general, the methodology implemented can be used for surgical planning and thus avoid trial and error procedures that may put the patient's health at risk. Also as a communication tool to explain to the patient the surgical procedures that will be submitted. In addition, it can be used for teaching purposes for the training of students, making learning processes more effective in the clinical setting that in turn would result in better results for patients.